ENT600: Swakiddo Smart Watch / Mohamad Amir Hakim Ishak and Mohamad Ariff Mohamad Noh - Ishak, Mohamad Amir Hakim; Mohamad Noh, Mohamad Ariff (2016)
Based on statistic made by Polis Di Raja Malaysia (PDRM), cases regarding missing children is increasing every year. This issue came from a lot of reasons, mostly because of lack of supervision from parents. A lot of methods have been introduced and a lot of campaign were invented to overcome this issue, however, until now the solution for this issue are still unresolved. This lead to the team to invent a product to help parents in order to supervise their kids even from far distances. That product is Swakiddo Smart Watch. With the existence of Swakiddo Smart Watch, parents are no longer need to be with their children all the time just to ensure their safety. In fact, they can also supervise their kids from distances through this smart watch which a GPS tracker were build-in in this product.